The Influence of Retirement Planning Programs on Retirement Planning and Attitude towards Retirement among Employees of Selected Ghanaian Organizations - Appiah-Ansong, J. (University of Ghana, 2014)
The study examined the influence of Retirement Planning Programs (RPPs) on retirement planning and attitude towards retirement among some employees in Ghana. Two hundred and fifty-eight (258) workers consisting of 154 who have attended RPPs and 104 who have never attended RPPs were used for the study. Findings indicated that workers who have attended RPPs engaged more in retirement planning and had positive attitude towards retirement compared to those who have never attended RPPs. Results also indicated that among those who have attended RPPs, males, older workers and high income earners engaged more in retirement planning and had positive attitude towards retirement compared to females, younger workers and low income earners. Level of education, marital status and number of dependants were not significant predictors of retirement planning and attitude towards retirement. Implications of the study were discussed.
Thesis (MPhil) - University of Ghana, 2014